Persistent diarrhea in living donors after donor hepatectomy: natural course and analysis of predisposing risk factors - Wang, Szu-Han; Lin, Ping-Yi; Chen, Yao-Li; Huang, Mei-Feng; Hsieh, Chia-En; Chen, Chih-Cheng (International Surgery Journal, 2020)
Background: Diarrhea is a frequent but overlooked complication of living liver donation. Thus, this retrospective study aimed to report the natural course of diarrhea and examined predictors of persistent diarrhea after living donor hepatectomy. Methods: We enrolled 79 donors who underwent living donor hepatectomy between 2010 and 2015 at a single medical center and had diarrhea symptoms after hepatectomy. The Chinese version of the gastrointestinal quality of life index (GIQLI) was applied to evaluate the effect of diarrhea on quality of life. Results: The onset of diarrhea was post-donation 1.1±0.3 months. According to their duration of diarrhea, donors were further classified into two groups: the healed and the persistent diarrhea group, the ratio was 36 to 43 (45.6% versus 54.4%). A donor who followed a low-fat diet had a protective effect on persistent diarrhea (odds ratio [OR] =0.18, 95% confidence interval: 0.04-0.66). Compared to healed diarrhea donors, donors with persistent diarrhea had lower GIQLI scores in the domains of physical (2.3 versus 1.9) and social functions (2.5 versus 2.3). Receiver operating characteristic curves for the duration of diarrhea after liver donation indicated that a donor was likely to develop a persistent diarrhea status if the duration of the diarrhea reached 12.5 months. Conclusions: A donor not following a low-fat diet can be independently predictive for persistent diarrhea after living donor hepatectomy. Besides, a donor with persistent diarrhea after hepatectomy is more likely to report lower GIQLI scores in physical and social functions.